2020
DOI: 10.3390/jcm9092752
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chest Trauma and Overweight on Mortality and Outcome in Severely Injured Patients

Abstract: The morbidity and mortality of severely injured patients are commonly affected by multiple factors. Especially, severe chest trauma has been shown to be a significant factor in considering outcome. Contemporaneously, weight-associated endocrinological, haematological, and metabolic deviations from the norm seem to have an impact on the posttraumatic course. Therefore, the aim of this study was to determine the influence of body weight on severely injured patients by emphasizing chest trauma. A total of 338 sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…Additionally, the present study revealed that MT patients with high subcutaneous fat tissue were in need of ventilation for a longer period and had a prolonged stay in the ICU and in hospital. These findings are in line with previously published observations on obese trauma patients [ 42 , 43 , 44 ]. As an underlying cause, Covarrubias et al reported on obesity being responsible for decreased chest wall compliance, decreased lung volume, increased oxygen consumption, increased respiratory rate, mild hypoxemia, and increased airway resistance [ 44 ].…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, the present study revealed that MT patients with high subcutaneous fat tissue were in need of ventilation for a longer period and had a prolonged stay in the ICU and in hospital. These findings are in line with previously published observations on obese trauma patients [ 42 , 43 , 44 ]. As an underlying cause, Covarrubias et al reported on obesity being responsible for decreased chest wall compliance, decreased lung volume, increased oxygen consumption, increased respiratory rate, mild hypoxemia, and increased airway resistance [ 44 ].…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have identified these changes, and determined that changes in the cardiovascular and pulmonary systems have the greatest impact on patient's prognosis [14,15]. In this current study the GCS and chest injury were independent risk factors of mortality which is similar to previous studies [9,16].…”
Section: Discussionsupporting
confidence: 85%
“…Our ndings are inconsistent with the "armor phenomenon," "cushion effect," "reverse epidemiology," and "obesity paradox," suggesting a potential protective bene t of childhood obesity regarding trauma. Multiple authors describe such a protective effect of obesity in trauma and intensive care [20,21]. For example, pediatric obese patients had the lowest mortality on univariate analysis and were non-inferior to healthy weight controls; the Injury Severity Score (ISS) was lowest in the obese group; and Hospital Length of Stay, ICU Length of Stay, and ventilator days were no different than with healthy weight patients [22].…”
Section: Discussionmentioning
confidence: 99%